On the derivation of class diagrams from use cases and logical software architectures - Santos, Maribel Yasmina (2010)
The transformation of user requirements into system requirements models can be achieved using the 4-Step Rule Set (4SRS) method that transforms UML use case diagrams into system-level object diagrams. These diagrams represent the logical architecture of the system, integrating the system-level entities, their responsibilities and the relationships among them. The logical architecture captures the system functional requirements and its nonfunctional intentionalities. Although contributing to the formalization of the design of software architectures, the 4SRS method needs to be extended in order to support the design of the database subsystems that may be considered pertinent within the specified logical architecture. This paper presents the extension of the 4SRS method to support the construction of the class diagram that complements the logical architecture, and shows, through the presentation of a demonstration case, the applicability of the proposed approach.